2020
DOI: 10.1108/pr-01-2020-0026
|View full text |Cite
|
Sign up to set email alerts
|

Cyberloafing in public sector of developing countries: job embeddedness as a context

Abstract: PurposeThis study aims to investigate the possible negativity of job embeddedness in developing countries. Operationally, the study aimed to configure the relationship between job embeddedness and cyberloafing with respect to both contextual (job satisfaction) and individual (internet addiction) factors.Design/methodology/approachIncorporating the conservation of resources theory and reactance theory into the theory of job embeddedness, the present study adopted a resource-based approach to job embeddedness to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 134 publications
(252 reference statements)
0
9
0
Order By: Relevance
“…The concept of cyberloafing has been examined through multiple theoretical lenses, such as the general theory of crime (Restubog et al, 2011), social learning theory (Khansa et al, 2017), conservation of resources theory (Agarwal and Avey, 2020;Koay et al, 2017;Karimi Mazidi et al, 2020;Zhou et al, 2021) and theory of interpersonal behavior (Betts et al, 2014;Moody and Siponen, 2013). Some scholars have also utilized dual theoretical lenses to examine this behavior.…”
Section: Theoretical Grounding and Contextual Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of cyberloafing has been examined through multiple theoretical lenses, such as the general theory of crime (Restubog et al, 2011), social learning theory (Khansa et al, 2017), conservation of resources theory (Agarwal and Avey, 2020;Koay et al, 2017;Karimi Mazidi et al, 2020;Zhou et al, 2021) and theory of interpersonal behavior (Betts et al, 2014;Moody and Siponen, 2013). Some scholars have also utilized dual theoretical lenses to examine this behavior.…”
Section: Theoretical Grounding and Contextual Differencesmentioning
confidence: 99%
“…According to Vitak et al (2011), there is a differential effect of antecedents like socio-demographic factors, Internet utility and routine Internet use on the jobs that require repetitive actions visa-vis creativity. Studies have determined that cyberloafing is predicted by an employee's organizational commitment (Hensel and Kacprzak, 2020), job embeddedness (Karimi Mazidi et al, 2020;Saghih and Nosrati, 2020) and identification with the job characteristics and stressors (Zhou et al, 2021), such as role conflict (Henle and Blanchard, 2008), job (Hensel and Kacprzak, 2020) or role overload (Varghese and Barber, 2017) and underload (Pindek et al, 2018). For instance, Elrehail et al (2021) found job demands, as well as stress, increased cyberloafing, while job resources and work engagement decreased this behavior.…”
Section: Peer Co-workermentioning
confidence: 99%
“…Actually, ICT elements introduced to employees with the aim to facilitate their working process and progress might have an adverse effect in reality and drive them to engage in production-deviant behaviours [ 12 ]. This issue is especially critical in integrating new technological tools and smartphones for work, which has turned into a standard practice for realising personal matters while working [ 13 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…These deviant use, especially smartphones during work, with social, informational, leisure or emotional purposes, could even develop into dependences related to the new technologies, further affecting employees’ work progress [ 14 , 15 ]. This situation is expected to arise in workplaces that are considered somewhat unfavourable, such as the case of the currently isolated work-from-home [ 12 , 16 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…We used Lim and Teo (2005) 3-item scale to measure cyberloafing of the third party. Participants were asked to report the frequency of their engagement in cyberloafing behaviors using a scale ranging from “1 Never” to “5 Very Frequently.” This scale has been widely used in previous cyberloafing research ( Karimi Mazidi et al, 2021 ). The Cronbach’s alpha value of this scale is 0.916.…”
Section: Methodsmentioning
confidence: 99%